IMPLEMENTATION OF DMAIC METHODOLOGY TO RESOLVE STOCK OPNAME DISCREPANCIES AT PT XYZ WAREHOUSE (POLITEKNIK LP3I JAKARTA, 2026)
opname discrepancies and to evaluate the changes in stock opname results before and after the application of DMAIC in inventory control at PT XYZ warehouse. The research design used is action research with a mixed-methods approach. The research data sources consist of primary and secondary data obtained through observation, interviews, document analysis, and focus group discussions (FGD). The research results show that the main causes of stock discrepancies are operators forgetting to record materials, accumulation of materials in one address, suboptimal material recording, and limited storage area capacity. The proposed improvements include dividing operator tasks, grouping materials and limiting storage capacity in one address, real-time material recording, implementing 3S, periodic address updates, and cycle counting. The implementation of the proposed improvements was able to reduce the stock discrepancy rate from -17% to -5%, or a decrease in the stock discrepancy rate by 12 percentage points. The recommendation given is that the company needs to use consistent strapping for pipe materials, optimize real-time material recording, and continue implementing the 5S principles (Seiri, Seiton, Seiso, Seiketsu, Shitsuke).